The need for local communities’ involvement in the future of real cultural heritage - Ćwik, Aleksandra (Kultura-Społeczeństwo-Edukacja, 2020)
The discussion about cultural heritage versus development has been touched upon in many publications, and the role of cultural heritage is being deployed increasingly into transforming mere development efforts into efforts for sustainable development. By analysing recent literature which indicates the need for facilitation of cooperation between authorities and local communities, the theory of ownership and value of cultural heritage, and the close relationship between heritage protection and sustainable development, the article aims to discuss the role of the local community in managing monuments. The most relevant conclusions include the link between the protection of cultural heritage and the improvement of the quality of life of residents, their sense of identity and more durable bonds with the place of residence and the strife toward the achievement of local, sustainable development goals.